EKSPLORASI TUMBUHAN OBAT DI KAWASAN GUNUNG SIBUATAN, KECAMATAN MEREK, KABUPATEN KARO, SUMATERA UTARA - Eben Ezer Silaban; Yunus Afifuddin; Ridwanti Batubara (Program studi Kehutanan USU, 2015)
The research of medicinal plants has been carried out in the mountain region Sibuatan, district Karo. The research aimed to identified the types of medicinal plants in mountain Sibuatan. Basic research methods in the development of medicinal plants had two stages. The first stage is the aspect of local knowledge with local knowledge survey. The second stage is the aspect of biodiversity with the analysis of vegetation data collection. They are 16 type of medicinal plants in mountain regions Sibuatan : Rubus reflexus, Impatiens balsamina, Nicolaia speciosa, Vitis gracilis, Solanum verbacifolium, Eupatorium odoratum, Nepenthes spectabilis, Nepenthes tobaica, Nepenthes gymnamphora, N.spectabilis x N. gymnamphora, Calamus diepenhorstii, Leersia hexandra, Melastoma candidum, Sida rhombifolia, Curculigo sp, Macodes petola. Keywords: Medicinal Plants, Mountain Regions Sibuatan, species.